The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1103/physreve.94.033111
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic coarsening arrested by viscous fingering in partially miscible binary mixtures

Abstract: We study the evolution of binary mixtures far from equilibrium, and show that the interplay between phase separation and hydrodynamic instability can arrest the Ostwald ripening process characteristic of nonflowing mixtures. We describe a model binary system in a Hele-Shaw cell using a phase-field approach with explicit dependence of both phase fraction and mass concentration. When the viscosity contrast between phases is large (as is the case for gas and liquid phases), an imposed background flow leads to vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…6c. A similar phenomenon has been observed in immiscible two phase systems, where the thermodynamics couples to the flow [35]. For C ≥ 200 mM, we observe longer and narrower fingers, essentially the same as Fig.…”
supporting
confidence: 88%
“…6c. A similar phenomenon has been observed in immiscible two phase systems, where the thermodynamics couples to the flow [35]. For C ≥ 200 mM, we observe longer and narrower fingers, essentially the same as Fig.…”
supporting
confidence: 88%
“…In the bulk, the scaling regimes that ensue at long times are relatively well understood [21]. While it has been shown that hydrodynamic instabilities may arrest the coarsening process [76], the role of wetting conditions on liquid-vapor transitions in porous media remains largely unexplored. The practical relevance of these phase ordering processes lies in the fact that they may control the initial distribution of fluids within the pore space as well as phase 084302-13 connectivity.…”
Section: Spinodal Decomposition Of a Van Der Waals Fluid In A Poromentioning
confidence: 99%
“…After the initial separation phase the pore domains occupied by the different phases will grow in a coarsening process that evolves towards the minimization of interfacial energy. In the bulk, the scaling regimes that ensue at long times are relatively well understood [21], although hydrodynamic instabilities may arrest the classical coarsening process [76].…”
Section: Introductionmentioning
confidence: 99%
“…The driving force is the capillary pressure difference between the bubbles (Figures 1a-1c). At equilibrium, Ostwald ripening leads to the formation of a single large bubble that may become hydrodynamically unstable (Fu et al, 2016). In the presence of confinement, however, the behavior of Ostwald ripening is modulated such that stable bubble configurations, with uniform capillary pressure, can exist.…”
Section: 1029/2019gl085175mentioning
confidence: 99%
“…Correspondence to: K. Xu While it is known that capillary trapping is hydrodynamically stable, its thermodynamic stability has been the subject of investigation only recently (Xu et al, 2017, de Chalendar et al, 2018, Garing et al, 2017. In the absence of geometric confinement, Ostwald ripening (Fu et al, 2016, Voorhees, 1985, Voorhees, 1992 is the mechanism that causes the diffusion of CO 2 from small bubbles towards large bubbles. The driving force is the capillary pressure difference between the bubbles (Figures 1a-1c).…”
Section: 1029/2019gl085175mentioning
confidence: 99%